LE135, a retinoid acid receptor antagonist, produces pain through direct activation of TRP channels. (March 2014) - Yin, Shijin; Luo, Jialie; Qian, Aihua; Yu, Weihua; Hu, Hongzhen
<x xml:space="preserve">Abstract</x> Background and Purpose Retinoids, through their activation of retinoic acid receptors (RARs) and retinoid X receptors, regulate diverse cellular processes, and pharmacological intervention in their actions has been successful in the treatment of skin disorders and cancers. Despite the many beneficial effects, administration of retinoids causes irritating side effects with unknown mechanisms. Here, we demonstrate that LE135 [4‐(7, 8, 9, 10‐tetrahydro‐5, 7, 7, 10, 10‐pentamethyl‐5H‐benzo[e]naphtho[2, 3‐b][1, 4]diazepin‐13‐yl)benzoic acid], a selective antagonist of RARβ, is a potent activator of the capsaicin (TRPV1) and wasabi (TRPA1) receptors, two critical pain‐initiating cation channels. Experimental Approach We performed to investigate the excitatory effects of LE135 on TRPV1 and TRPA1 channels expressed in HEK293T cells and in dorsal root ganglia neurons with calcium imaging and patch‐clamp recordings. We also used site‐directed mutagenesis of the channels to determine the structural basis of LE135‐induced activation of TRPV1 and TRPA1 channels and behavioural testing to examine if pharmacological inhibition and genetic deletion of the channels affected LE135‐evoked pain‐related behaviours. Key Results LE135 activated both the capsaicin receptor (TRPV1) and the allyl isothiocyanate receptor (TRPA1) heterologously expressed in HEK293T cells and endogenously expressed by sensory nociceptors. Mutations disrupting the capsaicin‐binding site attenuated LE135 activation of TRPV1 channels and a single mutation (K170R) eliminated TRPA1 activity evoked by LE135. Intraplantar injection of LE135 evoked pain‐related behaviours. Both TRPV1 and TRPA1 channels were involved in LE135‐elicited pain‐related responses, as shown by pharmacological and genetic ablation studies. Conclusions and Implications This blocker of retinoid acid signalling also exerted non‐genomic effects through activating the pain‐initiating TRPV1 and TRPA1 channels.